Women and Resilience on Pandemic Covid-19 Disaster: Feminist Participatory Action (FPA) - lestariyanti, elina; Hidayatullah, Ahmad Fauzan; Saptaningtyas, Haryani; Rohman, Isa Aulia (PALASTREN: Jurnal Studi Gender, 2022)
Women are the group that receives double impacts than men in disaster situations, including the Covid-19 pandemic. On the other hand, women have bigger potentials to participate in the implementation of the Covid-19 pandemic disaster management. This article explores women's resilience initiatives in the face of the Covid-19 pandemic disaster situation. This study used a descriptive narrative method to explain the initiative of the women community assisted by LRC-KJHAM in Central Java, Indonesia. The results showed that the women's community through the feminist participatory action (FPA) took the initiative and adaptive activities during the Covid-19 pandemic, including through education consist online discussions, counseling and campaigns and promote economic empowerment such as online markets, MSMEs, health protocol equipment, women's planting movements). In this article,  Feminists Participatory Action means the collection of some actions which is based on the data collected by vulnerable women and following by distributing some actions as part of their social assistance, such as through the provision of temporary shelters for women victims of domestic violence during the pandemic.